Synthesis and characterization of π–extended “earring” subporphyrins - Guan, Haiyan; Zhou, Mingbo; Yin, Bangshao; Xu, Ling; Song, Jianxin (Beilstein Journal of Organic Chemistry, 2018)
A π-extended “earring” subporphyrin 3 was synthesized from β,β′-diiodosubporphyrin and diboryltripyrrane via a Suzuki–Miyaura coupling and following oxidation. Its Pd complex 3Pd was also synthesized and both of the compounds were fully characterized by 1H NMR, MS and X-ray single crystal diffraction. The 1H NMR spectra and single crystal structures revealed that aromatic ring current did not extend to the “ear” in both of the two compounds. Their UV–vis/NIR spectra were recorded and the absorption of both compounds is extended to the NIR region and that the absorption of 3Pd is further red-shifted and more intense.
Keywords: aromaticity; earring subporphyrin; π-extended; supramolecular chemistry